2021
DOI: 10.1016/j.combustflame.2021.111581
|View full text |Cite
|
Sign up to set email alerts
|

Experimental and kinetic modeling study of n-hexane oxidation. Detection of complex low-temperature products using high-resolution mass spectrometry

Abstract: HAL is a multi-disciplinary open access archive for the deposit and dissemination of scientific research documents, whether they are published or not. The documents may come from teaching and research institutions in France or abroad, or from public or private research centers. L'archive ouverte pluridisciplinaire HAL, est destinée au dépôt et à la diffusion de documents scientifiques de niveau recherche, publiés ou non, émanant des établissements d'enseignement et de recherche français ou étrangers, des labor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1

Relationship

4
3

Authors

Journals

citations
Cited by 15 publications
(20 citation statements)
references
References 57 publications
0
20
0
Order By: Relevance
“…We have considered that the chemical formulae detected in this work for these isomers correspond mostly to KHPs. This assumption is based on results of simulations performed for n-hexane under conditions close to those of the present study [ 23 ] using a literature mechanism [ 18 ], including the formation of functionalized cyclic ethers (hydroperoxy and di-hydroperoxy-cyclic ethers). The model predicted 16 and 160 times less hydroperoxy and di-hydroperoxy-cyclic ethers, respectively, than KHPs.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We have considered that the chemical formulae detected in this work for these isomers correspond mostly to KHPs. This assumption is based on results of simulations performed for n-hexane under conditions close to those of the present study [ 23 ] using a literature mechanism [ 18 ], including the formation of functionalized cyclic ethers (hydroperoxy and di-hydroperoxy-cyclic ethers). The model predicted 16 and 160 times less hydroperoxy and di-hydroperoxy-cyclic ethers, respectively, than KHPs.…”
Section: Resultsmentioning
confidence: 99%
“…The liquid samples were stored in a freezer (−15 °C) and analyzed by both HPLC and UHPLC coupled to high resolution mass spectrometry (Orbitrap Q-Exactive ® , Thermo Fisher Scientific, Waltham, MA, USA). This analytical protocol has been used in previous works of ours where its effectiveness was demonstrated [ 16 , 23 ]. The JSR experimental conditions are shown in Table 1 .…”
Section: Methodsmentioning
confidence: 99%
“…The present experiments were carried out in a fused silica jet-stirred reactor (JSR) setup presented earlier (Dagaut et al, 1986;Dagaut et al, 1988) and used in previous studies (Dagaut et al, 1987;Benoit et al, 2021;Belhadj et al, 2021). The two isomers α-pinene and limonene were studied separately.…”
Section: Oxidation Experimentsmentioning
confidence: 99%
“…In low-temperature combustion (cool flame) the formation of oxidized organic molecules (OOM) is mainly attributed to autoxidation reactions (Belhadj et al, 2021;Benoit et al, 2021), whereas in atmospheric chemistry, it is only relatively recently that this pathway has been considered (Vereecken et al, 2007;Crounse et al, 2013;Jokinen et al, 2014a;Berndt et al, 2015;Jokinen et al, 2015a;Berndt et al, 2016;Iyer et al, 2021). Also, it has been identified that highly oxygenated molecules (HOMs), a source of secondary organic aerosols (SOA), can result from autoxidation processes (Wang et al, 2021;Tomaz et al, 2021;Bianchi et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation